Perfil farmacocinético do tramadol e o-desmetiltramadol após administração intravenosa em jumentos (equus asinus) - Mouta, Andressa Nunes (2019)
Donkeys are rustic animals that quickly adapt to adverse conditions and intense traction work, and are constantly exposed to painful clinical conditions, so it is of paramount importance to treat them adequately through the use of appropriate analgesics. Tramadol is a centrally acting opioid analgesic widely used to treat acute and chronic pain in humans and animals. Its hepatic metabolization results in several metabolites, the main one being the active metabolite O-desmethyltramadol (M1), since it has higher affinity for opioid receptors. The aim of the present study was to describe the pharmacokinetics of tramadol and M1 following single intravenous administration of two distinct doses in donkeys. Ten adult, healthy, male and whole donkeys were used. In group T2, 8 animals received the 2 mg.kg-1 dose of tramadol and in group T4, the same 8 animals received the dose of 4 mg.kg-1, with an interval of 15 days between treatments. 10 ml of jugular vein blood were collected to obtain plasma and the samples were conditioned at -80 ° C for further pharmacokinetic analysis by ultra-efficient liquid chromatography coupled with a mass spectrometry detector (UPLC-MS/MS) using a non-compartmental model. Blood collection was performed at time 0 (prior to drug administration) and following the times: 5, 10, 20, 30, 40, 50 minutes, 1h, 1: 15h, 1: 30h, 1: 45h, 2h, 2:30 h, 3h, 4h, 6h, 8h, 12h, 24h and 48h. Adverse effects from drug administration were also observed. Tramadol and M1 were measured up to 48 hours and quantified up to 12 hours after administration. The 4 mg.kg-1 dose showed a significant increase in mean residual time (MRT0 → ∞) and time half-life elmmination (t1/2) for the metabolite. For tramadol, the mean maximum plasma concentration (Cmax), t1/2 and MRT0 → ∞ for 2 mg.kg-1 were 473,62ng/ml, 4,49h e 1,44 h, while at 4mg dose. kg-1 were 7553,93 ng/ml 5,99 h e 2,27 h. For M1, Cmax, t1/2, Tmax and MRT0 → ∞ for the lowest dose were 90,37 ng/ml, 2,50 h, 0,94 h e 3,88 h, while for the highest dose they were 109,62 ng/ml, 6,95h, 1,19 h e 7,42 h. At the lower dose, one animal presented ataxia and muscle spasms, while at the higher dose, seven animals presented these effects. Tramadol and M1 reached plasma concentrations considered effective for analgesia. Dosing intervals of approximately 2.5 and 6.9 hours are suggested for the 2 and 4 mg/kg-1 doses respectively. A longer tramadol administration time is required to avoid adverse effects.